The effect of anodization parameters on the aluminum oxide dielectric layer of thin-film transistors - Gomes, Tiago C. [UNESP]; Kumar, Dinesh; Alves, Neri [UNESP]; Kettle, Jeff; Fugikawa-Santos, Lucas [UNESP] (MyJove, 2020)
Aluminum-oxide (Al2O3) is a low cost, easily processable and high dielectric constant insulating material that is particularly appropriate for use as the dielectric layer of thin-film transistors (TFTs). Growth of aluminum-oxide layers from anodization of metallic aluminum films is greatly advantageous when compared to sophisticated processes such as atomic layer deposition (ALD) or deposition methods that demand relatively high temperatures (above 300 °C) such as aqueous combustion or spray-pyrolysis. However, the electrical properties of the transistors are highly dependent on the presence of defects and localized states at the semiconductor/dielectric interface, which are strongly affected by the manufacturing parameters of the anodized dielectric layer. To determine how several fabrication parameters influence the device performance without performing all possible combination of factors, we used a reduced factorial analysis based on a Plackett-Burman design of experiments (DOE). The choice of this DOE permits the use of only 12 experimental runs of combinations of factors (instead of all 256 possibilities) to obtain the optimized device performance. The ranking of the factors by the effect on device responses such as the TFT mobility is possible by applying analysis of variance (ANOVA) to the obtained results.
Keywords: Aluminum oxide; Anodization; ANOVA; Chemistry; Dielectric layer; Issue 159; Thin-film transistor; Zinc oxide